Long memory volatility of gold price returns: how strong is the evidence from distinct economic cycles? - Bentes, S. R. (2017)
This paper examines the long memory behavior in the volatility of gold returns using daily data for the period 1985–2009. We divided the whole sample into eight sub-samples in order to analyze the robustness and consistency of our results during different crisis periods. This constitutes our main contribution. We cover four major world crises, namely, (i) the US stock market crash of 1987; (ii) the Asian financial crisis of 1997; (iii) the World Trade Center terrorist attack of 2001 and finally, (iv) the sub-prime crisis of 2007, in order to investigate how the fractional integrated parameter of the FIGARCH(1,d,1) model evolves over time. Our findings are twofold: (i) there is evidence of long memory in the conditional variance over the whole sample period; (ii) when we consider the sub-sample analysis, the results show mixed evidence. Thus, for the 1985–2003 period the long memory parameter is positive and statistically significant in the pre-crisis sub-samples, and there is no evidence of long memory in the crisis sub-sample periods; however the reverse pattern occurs for the 2005–2009 period. This highlights the unique characteristics of the 2007 sub-prime crisis.